Development and evaluation of a loop-mediated isothermal amplification (LAMP) method for Candida glabrata detection - Yahaya, H.; Cheah, Y.K.; Chee, H.Y.; Than, L.T.L. (Springer Science and Business Media Deutschland, 2024)
Purpose: Loop-mediated isothermal amplification (LAMP) is a simple and rapid nucleic acid method for DNA amplification at a constant temperature. The “gold standard” culture method for yeast detection, has low sensitivity with severe consequences, increasing morbidity and mortality rates. Here, we report the development of a LAMP method for the specific detection of C. glabrata. Methodology: The specific LAMP primers for C. glabrata detection were designed and evaluated. Results: The LAMP assay accurately detected C. glabrata with no cross-reactivity with other Candida species. Conclusion: The developed molecular method would be a promising tool in the management of invasive candidiasis.